Análise de biomarcadores salivares e plasmáticos após realização de um esforço submáximo em mulheres com hipotireoidismo subclínico tratadas com L-tiroxina sódica - Lamounier, Romeu Paulo Martins Silva (2007)
Patients with subclinical hypothyroidism treated with sodium L-thyroxine realized test of physical effort in cycle ergometer to investigate the alterations in the concentrations of blood lactate; total protein, immunoglobulin A, nitric oxide, alpha-amylase activity, present in the saliva; and tolerance to the physical effort. We selected eight female volunteers aged 51.8 ± 4.9 years, TSH > 4.4 mU/dL, total T3 and free T4 in the plasma and without clinical signs of hypothyroidism. The values of blood lactate and salivary total protein was more raised (p<0.05) when compared before and after the administration of L-thyroxine in the realization of the effort test. The displacement for right of the point of threshold of blood lactate, salivary total protein and the increase of a stage of training in the incremental test reflected a greater adaptation to the exercise after the treatment. The values of blood lactate, salivary total protein and salivary nitric oxide, before and after the test, was greater when the volunteers was treatment with L-thyroxine (p<0.05). The values of salivary alpha-amylase activity and concentration of salivary immunoglobulin A, after and before the effort test, hadn t difference (p<0.05) in relation to the treatment with L-thyroxine. Some of biomarkers analyzed in this study had not alterations that indicated one better adaptation after the exercise. However, the treatment with L-thyroxine showed alterations of the salivary nitric oxide and the anaerobic threshold in the test of physical effort when evaluated by the measure of blood lactate and salivary total protein. These data showed that the replacement of L-thyroxine increases the tolerance to the physical effort.